Just One Thing: Twelve of the World's Best Investors Reveal the One Strategy You Can't Overlook - Mauldin John (John Wiley & Sons, 2006)
Whether from business-focused cable TV channels, newspapers, magazines, Web sites, or friends and family, investment advice comes these days from every corner. The nagging question for conscientious investors remains, though: how to separate good advice from bad? In a world of squawking television commentators and garish headlines, who and what should we trust? With Just One Thing, veteran investment writer John Mauldin offers his answer: take just the best advice, from the best investors, and discard everything else. Mauldin has solicited 12 leading investors for what each considers his most valuable insight or lesson over a long and illustrious investment career--the "one thing" he considers most important to investing--and gathered the tips for future generations of investors to learn.